Penguatan Karakter Anak Melalui Media Video Pembelajaran Di TK Annida Desa Rancabungur - Nita, Nita Nurmelida; Nisa, Syifa Zakiyatun; Fuadah, Sarah Salmatul; Pajririyah, Fadillah; Karimah, Syahadah Albaqiyatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This community service aims to strengthen the character of children at Annida Kindergarten by using video learning media. The method is the demonstration by using the video learning media which makes the atmosphere of the learning process more fun, interesting and efficient. The results showed that the use of digital audio-visual media is able to instill and strengthen the character of children at Annida Kindergarten. Therefore, learning by watching video can be used as an alternative for strengthening character in early childhood.